SOSIALISME ISLAM: PERSPEKTIF PEMIKIRAN POLITIK H.O.S. TJOKROAMINOTO - Firman Manan (Universitas Padjadjaran, 2016)
In several literatures of Indonesian political thought, the ideas of socialism has been claimed as the doctrine came from and influenced by western political thought. On the other side, Islam political thought has been seemed as the doctrine came from Indonesia traditional heritages. These view was rejected by H.O.S. Tjokroaminoto who argues that socialism has been established and flourished inthe Islamic tradition before it was developed in the West. This article tries to describe H.O.S. Tjokroaminoto’s political thought about Islamic socialism which was constructed in the Islamic tradition rooted from Al-Quran and As-Sunnah.